Next-Generation Aerodynamics for High-Performance Aircraft ‎and Space Launch Vehicles - Rahman, Dr. F; Shivaji , Ghorpade Bipin; Benerjee , Sayanti (International Journal of Basic and Applied Sciences, 2025)
This paper looks at the progress of aerodynamic tech on high-performance aircraft and space launch vehicles. It uses new aerodynamic ‎designs, CFD models, and experimental testing to advance aviation and space exploration. It examines pilots' challenges in atmospheric and ‎space launches, prioritizing high-speed airflow in supersonic and hypersonic conditions. Research tackles drag control, heat dissipation, and ‎aerodynamic stability to optimize aircraft performance at high speeds. Modern materials like lightweight composites and heat-resistant ‎coatings are featured in the article to improve operational durability and performance. The article discussed adaptive surface control systems ‎capable of morphing a wing's shape during flight to enhance lift and minimize drag. This allows for improved maneuverability, increased ‎fuel efficiency, and better mission accomplishment metrics. By using computational fluid dynamics (CFD), one can limit empirical testing ‎for a given research problem. The integration of new materials and technological advances in aviation and aerospace results in significant ‎performance advances while also achieving sustainable operations.
Keywords: High-Speed Aerodynamics; Supersonic and Hypersonic Flight; Computational Fluid Dynamics (CFD); Adaptive Surface Control; ‎Lightweight Composite Materials; Drag and Heat Management